Thickness Dependent Structural and Electrical Properties of Magnetron Sputtered Nanostructured CrN Thin Films - Akkera,Harish Sharma (2017)
In the present work, we have investigated the structural and electrical properties of CrN thin films for a thickness t in the 30-220 nm range, grown on Si (100) substrates. The CrN/Si (100) films exhibits a structural transition from hexagonal phase (β-Cr2N) to cubic phase (CrN) with the increasing in film thickness, the change in structural transition is attributed to the decrease of film-substrate interfacial strain. From electrical resistivity measurements, the thickness of 150 nm CrN/Si (100) film shown the metal-semiconductor phase transition at around 250 K with energy band gap (Eg) 81 meV in semiconducting region, whereas the thickness of 30, 110 and 220 nm CrN/Si(100) films were shown only semiconducting behaviour for whole temperature range of 50-400 K. On the other hand, a clear grain size was increased in CrN/Si films with increasing thickness and its influence on transport properties was also seen. The possibility of phase transition and occurrence of semiconducting behaviour in the CrN films were analysed.